2010
DOI: 10.2478/s11536-009-0098-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in substance P-immunoreactive nerve structures of the rat recto-anal region

Abstract: AbstractThe recto-anal region is innervated by extrinsic and intrinsic nerves and a number of neuropeptides including substance P (SP) have been suggested to participate in the regulation of intestinal movements. We examined the age-related changes in the distribution of SP-immunoreactive nerve structures in the distal part of the rat large intestine. Using immunohistochemistry, the presence of SP was studied in fresh tissues from Wistar rats at different ages taken at three sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
4
1
0
Order By: Relevance
“…Similar to our findings, an absence of significant SP‐immunostaining in the myenteric neuronal bodies has previously been reported (Lazarov et al, 2009). Conversely, another study has shown an intense staining of myenteric neuronal somata (Hens et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similar to our findings, an absence of significant SP‐immunostaining in the myenteric neuronal bodies has previously been reported (Lazarov et al, 2009). Conversely, another study has shown an intense staining of myenteric neuronal somata (Hens et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…In this regard, the present findings strongly reinforce the suggestion that SP-positive structures are an important component of the enteric circuitry. Similar to our findings, an absence of significant SPimmunostaining in the myenteric neuronal bodies has previously been reported (Lazarov et al, 2009). Conversely, another study has shown an intense staining of myenteric neuronal somata (Hens et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2B). Such negative perikaryal staining has been described in previous studies (27,28). On the other hand, positive staining has been observed in other experiments (29,30).…”
Section: Peptidergic Transmission In the Myenteric Plexussupporting
confidence: 79%
“…At the time of sacrifice, all the animals were anesthetized with Thiopental (50 mg/kg) intraperitoneally, and the animals were transcardially perfused, first, with warm heparinized 0.05 mol/l PBS (pH 7.4), followed by freshly prepared 4% paraformaldehyde in 0.1 mol/l phosphate buffer [18]. The stomachs were dissected and rinsed with PBS (pH 7.4), poured into the gastric cavity with 40 g/l paraformaldehyde (until three to four times of normal stomach volume), and placed in the same fixative for 4-6 h (4ºC).…”
Section: Animal Usedmentioning
confidence: 99%